2019
DOI: 10.2147/ndt.s200360
|View full text |Cite
|
Sign up to set email alerts
|

<p>Cardiac dysautonomia in depression – heart rate variability biofeedback as a potential add-on therapy</p>

Abstract: Depressive disorders are among the most important health problems and are predicted to constitute the leading cause of disease burden by the year 2030. Aside significant impact on quality of life, psychosocial well-being and socioeconomic status of affected patients, depression is associated with impaired cardiovascular health and increased mortality. The link between affective and cardiovascular disease has largely been attributed to dysregulation of the autonomic nervous system resulting in a chronic shift t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 166 publications
(149 reference statements)
1
62
0
2
Order By: Relevance
“…Some research reported that HF and LF were significantly reduced in patients with chronic fatigue syndrome (CFS) or anxiety, which discovered there were an imbalance of cardiac autonomic nerves and the decreased cardiac vagus function in some mental illness [33,34]. Moreover, a recent study reported the average heart rate was increased in patients with depression [35]. In the present study, our results demonstrated that both the HF and LF of the subjects with depression were significantly reduced, and the average heart rate was significantly increased, confirming that depression could also cause an imbalance of cardiac autonomic nerves and the decreased cardiac vagus function in college students.…”
Section: Discussionmentioning
confidence: 99%
“…Some research reported that HF and LF were significantly reduced in patients with chronic fatigue syndrome (CFS) or anxiety, which discovered there were an imbalance of cardiac autonomic nerves and the decreased cardiac vagus function in some mental illness [33,34]. Moreover, a recent study reported the average heart rate was increased in patients with depression [35]. In the present study, our results demonstrated that both the HF and LF of the subjects with depression were significantly reduced, and the average heart rate was significantly increased, confirming that depression could also cause an imbalance of cardiac autonomic nerves and the decreased cardiac vagus function in college students.…”
Section: Discussionmentioning
confidence: 99%
“…Dysautonomia in PE may be alleviated by an easy-to-learn technique, the heart rate variability biofeedback. It has been shown to improve both autonomic functioning and perinatal anxiety and depression (75, 76).…”
Section: Discussionmentioning
confidence: 99%
“…Higher HRV is observed in those who are more persistent in solving complex problems while intensive selfcontrol efforts are required [54]. A shift from parasympathetic to sympathetic autonomic activity resulting in cardiac dysautonomia is frequently found in depression [55]. Karavidas [56] stated that depression is associated with a decreased HRV.…”
Section: Heart Rate Variability (Hrv) and Respiratorymentioning
confidence: 99%